DIGITAL SUSTAINABILITY: A KNOWLEDGE WELL KNOWN TO THE COMPANIES AND THE INDIVIDUALS OF A COMMUNITY? - Basumatary, Anganjyoti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study is focused on Digital Sustainability. Being a new research topic for the researchers, it has yet to be fully studied. Digital Sustainability is a sub group of Sustainability. Hence the literature related to sustainability is firstly required to comprehend the ideology behind Digital Sustainability. It affects various sectors such as environment, economic, social and technological. The economy, society, environment and technology, all are within the encirclement of Digital Technology. This needs awareness, not only by the community but also by the companies. During usage of any a kind of technology related activity one must be able to understand its impact on both sides, the positive as well as the negative. In this 21st century, even the Corporate Social Responsibility (CSR) activities which are performed by the companies need to be sustainable not only physically but also digitally. The companies as well as the community must be aware of the electronic wastages that they have been compiling such as old computer parts, TV, Fridge and various other gadgets. The lesser the technological wastages, the lesser impact it would have on the economy, environment, society and technology. The environment needs to be taken care of as studies have found that AI used by the companies have led to change of climate in some regions. The economy needs constant refurbishing and growth. Digital Sustainability helps economic growth via reuse of the resources and share them equally. The society and technology are inseparable now and Digital Sustainability has become of utmost importance.